1974
DOI: 10.3758/bf03334273
|View full text |Cite
|
Sign up to set email alerts
|

The influence of preoperative learning on the recovery of a successive brightness discrimination

Abstract: Effects of shift in sucrose and saccharine concentrations on licking behavior in the rat.The recovery of a successive two-choice brightness discrimination following posterior neodecortication is significantly impaired if the reinforcement contingencies of the postoperative task are the reverse of those learned preoperatively. These results replicate a simultaneous two-choice brightness discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

1977
1977
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…The question was considered important for two principal reasons. First, even though striate cortex lesions may severely disrupt the performance of a learned brightness discrimination in the rat, certain aspects of this learning are apparently spared (LeVere, 1975;LeVere & Morlock, 1973, 1974. If certain aspects of the preoperative learning, notably those characterized as associations or engrams, may be spared following visual neodecortication, might not the animals' more fundamental psychophysical response to light be also spared?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question was considered important for two principal reasons. First, even though striate cortex lesions may severely disrupt the performance of a learned brightness discrimination in the rat, certain aspects of this learning are apparently spared (LeVere, 1975;LeVere & Morlock, 1973, 1974. If certain aspects of the preoperative learning, notably those characterized as associations or engrams, may be spared following visual neodecortication, might not the animals' more fundamental psychophysical response to light be also spared?…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has recently been shown that this postoperative recovery of function is not independent of the originally learned brightness discrimination, since animals postopera,tively. retrained on the reversal of the preoperative discrimination are severely impaired relative to animals postoperatively retrained on the original preoperative discrimination (LeVere & Morlock, 1973, 1974. Thus, while visual decortication may certainly disrupt the performance of a learned brightness discrimination, apparently much of the preoperatively learned behavior is just as certainly spared.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The results indicated that simply reinstating the preoperative motivation state is insufficient to allow the animal access to the preoperative memories. However, if the preoperative motivation state is reinstated and the animal is also provided rewards appropriate to that moii~ation, then the addition of another motivation and rewards will not prevent the retrieval of spared preoperative memories.The fact that visual decorticate rats are severely impaired when trained on the reversal of a preoperatively learned brightness discrimination demonstrates that this neocortical injury does not destroy the memories of the preoperatively learned behavior even though the lesioned animal is initially unable to perform the task (T. E. LeVere & Morlock, 1973, 1974. It would appear that lesions to other neocortical areas also do not destroy the memories of preoperatively learned behaviors.…”
mentioning
confidence: 99%
“…The fact that visual decorticate rats are severely impaired when trained on the reversal of a preoperatively learned brightness discrimination demonstrates that this neocortical injury does not destroy the memories of the preoperatively learned behavior even though the lesioned animal is initially unable to perform the task (T. E. LeVere & Morlock, 1973, 1974. It would appear that lesions to other neocortical areas also do not destroy the memories of preoperatively learned behaviors.…”
mentioning
confidence: 99%